1995
DOI: 10.1177/43.10.7560888
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of Na,K-ATPase in the gerbil cochlea.

Abstract: The transport enzyme Na,K-ATPase has been localized to several different cell types within the inner ear by enzyme cytochemistry, immunohistochemistry, and in situ hybridization. Although these histochemical procedures have provided a fairly consistent pattern of the enzyme's distribution, the precise location of Na,K-ATPase in the cell membrane of some polarized and non-polarized cell types remains uncertain. We addressed this problem in the gerbil cochlea using electron microscopic immunogold cytochemistry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 4 publications
3
44
1
1
Order By: Relevance
“…Thus, there does not seem to be a particular subcellular compartment to which NKAα3 expression is restricted in either the central or peripheral nervous system. Our findings are consistent with earlier research using immunocytochemistry that identified the NKAα3 in the SGNs and cochlear nerve in the gerbil (Schulte and Adams 1989;McGuirt and Schulte 1994;Nakazawa et al 1995), rat (ten Cate et al 1994;Peters et al 2001), and mouse (Erichsen et al 1996). NKAα immunoreactivity was localized to the nerve terminals underlying the IHCs and OHCs in the human cochlea (Weber et al 2001).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, there does not seem to be a particular subcellular compartment to which NKAα3 expression is restricted in either the central or peripheral nervous system. Our findings are consistent with earlier research using immunocytochemistry that identified the NKAα3 in the SGNs and cochlear nerve in the gerbil (Schulte and Adams 1989;McGuirt and Schulte 1994;Nakazawa et al 1995), rat (ten Cate et al 1994;Peters et al 2001), and mouse (Erichsen et al 1996). NKAα immunoreactivity was localized to the nerve terminals underlying the IHCs and OHCs in the human cochlea (Weber et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…3G). Although others have reported expression of the NKAα3 in the myelinated segments (Nakazawa et al 1995) and nodes of Ranvier (Schulte and Adams 1989) of the afferent fibers, our experiments showed NKAα3 immunoreactivity that was most intense in the initial segments of the afferent fibers directly contacting the IHCs and not enriched in the subsequent unmyelinated nodes.…”
Section: Nkaα3 Is Present In Type I Afferent Terminals Contacting Thecontrasting
confidence: 92%
See 3 more Smart Citations